Association of air pollution from a landfill site with changes in primary care consultation patterns - Kelvin P. Jordan; Sara Muller; Muhammad Usman; James Bailey; Claire Burton; Sarah A. Lawton; Christian D. Mallen; Kayleigh J. Mason; Simon Wathall; Danielle A. van der Windt (Discover Environment)
Abstract Background Waste landfill sites are associated with gaseous emissions and this air pollution can cause unpleasant smells (“malodour”). This causes concerns about its impact on the health of the local population. This study assessed change in general practice consultation behaviour during a period of increased complaints associated with air pollution at a UK landfill site. Methods The study period was October 2020 to December 2021. The age-sex standardised prevalence and incidence of consultations for mental health, respiratory, and other symptoms hypothesised to be impacted by the air pollution issues were determined and compared between: (i) 6 practices located close to the landfill site (zone A), (ii) 6 practices located a mid-distance from the site (zone B), (iii) 6 practices located further away and expected to have had less impact (zone C). Results There was an increased consultation for mental health problems in practices nearest to the landfill site compared to those furthest away, however, consultation frequencies for respiratory and other potentially associated symptoms were lower and likelihood of consultation was consistently highest in practices located in zone B. Conclusion This study showed limited evidence of an increase in recorded primary healthcare contacts for conditions and symptoms hypothesised to be connected to air pollution. It highlighted the challenges of examining impact of air pollution on the health of local populations. Since this study focussed on coded consultations in primary care and not symptoms present in the general population, an impact on the health of individuals cannot be ruled out.